Active surveillance and emerging medical treatment options for desmoid: when and for whom? - Bonvalot, Sylvie; Miah, Aisha; Kasper, Bernd (Current opinion in oncology, 2024)
Purpose of review - This article discusses the evolving approaches to desmoid tumors management, shedding light on recent developments. - Recent findings - Active surveillance has become the primary approach for managing primary peripheral desmoid tumors. This strategy was initially based on evidence from retrospective studies. Roughly 50% of cases managed with active surveillance show spontaneous stabilization or regression. Recent prospective trials conducted in Italy, The Netherlands, and France (2022-2023) confirm the efficacy of active surveillance, revealing 3-year progression-free survival rates ranging from 53.4 to 58%. For the patients under active surveillance, decisions regarding treatment are based on significant tumor growth or progressive symptoms. Moreover, three contemporary randomized trials investigated medical treatments for progressive or recurrent desmoid tumors. Sorafenib, pazopanib, and nirogacestat demonstrated clinical activity, as evidenced by favorable progression-free survival and objective response rates. - Summary - Active surveillance has solidified its position as the primary management approach for desmoid tumors, validated by three robust prospective studies. Three recent randomized trials explored medical treatment for progressive or recurrent desmoid tumors, revealing promising clinical activities.